A Sociolinguistics Analysis of Stereotypes in the Freedom Writers Movie - Puspitasari, Lintang Putri; Nugroho, Abdillah (Universitas Pendidikan Ganesha, 2023)
Stereotypes are viewed negatively since they indicate negative preconceptions about others. Hence, stereotypes are important to study because people might unknowingly employ stereotypes about others in regular encounters. Stereotypes are also found in many films, one of which is in the film